Association of acute phase reactants with prognostic scores in community acquired pneumonia - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2021)
Objective: To investigate the association of C-reactive protein and procalcitonin with commonly used prognostic scoring systems, hospitalisation and mortality in cases of community-acquired pneumonia. Methods: The prospective study was conducted from April 2014 to April 2015 at the emergency department of Marmara University Pendik Research and Training Hospital, Turkey, and comprised community-acquired pneumonia patients diagnosed according to the British Thoracic Society criteria. Prognosis was estimated using confusion, urea, respiratory rate, blood pressure and age >65, Pneumonia Severity Index-Pneumonia Patient Outcome Research Team score, and severe community-acquired pneumonia scores. Data was analysed using MedCalc 15.8. Results: Of the 203 patients assessed, community-acquired pneumonia was confirmed in 152(74.8%). Procalcitonin had moderate correlation with the three scales used (p<0.001), while C-reactive protein had weak correlation with them (p<0.004). Conclusion: Both procalcitonin and C-reactive protein levels were found to be correlated with prognostic risk scores.
Keywords: Pneumonia; C reactive protein; procalcitonin; PSI; CURB-65; SCAP; (JPMA 71; 614; 2021)